The Influence of Organic Cosolvent (Methanol) on the Adsorption of Carbofuran on Three Different Types of Indian Soils - R.P. Singh (Adsorption Science & Technology)
The adsorption of carbofuran on three different types of uncontaminated Indian soils (loam, silt clay loam, sandy loam) at various volume fractions (0.25, 0.50, 0.75, 1.0) of methanol (f S ) has been studied by the batch shake technique. The adsorption of carbofuran was higher on loam soil, followed by silt clay loam and sandy loam soils, and decreased with increasing f S values on all soils. From the adsorption data, adsorption partition coefficients K D (ml/g) were evaluated and the K D values converted to mole-based partition coefficients K m (mol/g). These values were utilised to test the cosolvent theory. The K m values for soils, when normalised on foc, gave values of K moc , and a plot of log K moc versus f S resulted in a single line whose equation was determined by linear regression analysis as log K moc = –1.12 + 2.84; r 2 = 0.96. The aqueous phase partition coefficient K Dw (mol/g) normalised on f ∞ for carbofuran extrapolated from this relationship was 4.1, The slope may be related to the effect of carbofuran solubility and to carbofuran–soil and solvent–soil interactions. The data presented suggested that methanol–soil interaction may not increase the accessibility of carbofuran to soil organic matter to the same extent as reported for less hydrophobic organic solutes.